Reproductive characteristics of Ethiopian highland sheep. I. Genetic parameters of testicular measurements in ram lambs and relationship with age at puberty in ewe lambs - Toe, F.; Rege, J.E.O.; Mukasa-Mugerwa, E.; Tembely, S.; Anindo, D.O.; Baker, R.L.; Lahlou-Kassi, A. (Elsevier, 2000)
A study was conducted to estimate heritabilities of, and genetic correlations among, body weight (WT) and testicular measurements - scrotal circumference (SC), testicular diameter (TD), testicular length (TL) and epididymal diameter (ED - in ram lambs between 6, 9 and 12 months old, and relationship of the testicular traits with age at puberty in ewe lambs (AP). Two fat-tailed sheep breeds, the Horro and Menz, indigenous to the Ethiopian highlands were studied. Experimental lambs were produced by mating 250 oestrus-synchronized ewes of each breed to 10 sires in a single-sire mating system over three mating periods which produced, for this study, a total of 361 ram lambs and 148 ewe lambs, with substantial pedigree information, in two dry seasons (October/November 1992 and 1993) and one wet season (June/July 1993). Mean AP was 322.7 days. Breed was not significant (P>0.05) for all testicular measurements, except ED at 9 months for which the Horro had a higher (P